Introduction to sport law - Spengler, John O. (John Otto) 1962-; Anderson, Paul M. (Paul Martin) 1969-; Connaughton, Daniel 1963-; Baker, Thomas A.
"This book aims to help students learn the common legal concepts taught in sport management curricula without the use of unnecessary legalese. Information and examples in the text challenge students to think about sport law concepts and apply them to the practical world of sport management"--Provided by publisher.
U.S. legal system -- Tort law and product liability -- Risk management -- Agency law -- Contract law -- Employment law -- Constitutional law -- Gender equity -- Intellectual property law -- Antitrust law -- Labor law.
CAC Camia (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Sports -- Law and legislation -- United States